Adsorption kinetics study of PAC-organic dye system - Kašpar, Stanislav; Jiránková, Hana; Doleček, Petr (University of Pardubice, 2009)
This paper deals with the study of organic dye adsorption from aqueous phase on powdered activated carbon. Theoretical part summarises the kinetic models mostly used for description of adsorption on powdered activated carbon. Sorptive capacity and adsorption kinetics were studied in experimental part. The rate constants of studied system Ostazine orange on PAC were estimated.